Air Canada : selling the company by the slice - Rosenthal, Jean W., 1945-; Bova, Francesco; Thomas, Jacob ([London] : SAGE, 2016)
Robert Milton had been fascinated by flying ever since childhood and dreamed of running an airline. But as he grew up and entered the industry, Milton came to see how poorly the major 'legacy' airlines performed financially. The romance of flying could not obscure the difficulty of sustaining a profit in this industry. After a series of jobs in the airline industry, Milton came to Air Canada in 1992. While COO of the airline, he became convinced that the various parts of the airline operated separately could be worth more than the combined company. Milton proposed that the company examine its various functional areas to find unrealized value in divisions that could be stand-alone entities. This case study examines this topic.
Originally Published in: Rosenthal, J. W., Bova, F., & Thomas, J. (2007). Air Canada: Selling the Company by the Slice. 07-038. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Air Canada; Airlines -- Management -- Case studies; Corporate divestiture -- Case studies